2021
DOI: 10.5114/ada.2021.107934
|View full text |Cite
|
Sign up to set email alerts
|

The importance of use of the FSFI questionnaire in gynecology and venerology: a pilot study

Abstract: Introduction The Female Sexual Function Index (FSFI) is recognized as an excellent tool for assessing female sexuality and screening female sexual dysfunction, but it also has important venereological implications as sexually transmitted diseases result from human behaviour in the sexual sphere. It is influenced by socio-economic, psychological and cultural factors. Aim To present the results of an attempt to implement FSFI in gynaecological practice. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…All six domains of female sexual function were assessed under only one corresponding head instead of validated standard 19 point FSFI. Jarząbek-Bielecka et al reported, "High percentage of sexually active Polish women presented with FSFI below the threshold; suggesting some grade of sexual dysfunction [7]. The study also concluded that gynaecological and sexually transmitted infections medical history should be extended to include issues related to female sexual function".…”
Section: Discussionmentioning
confidence: 93%
“…All six domains of female sexual function were assessed under only one corresponding head instead of validated standard 19 point FSFI. Jarząbek-Bielecka et al reported, "High percentage of sexually active Polish women presented with FSFI below the threshold; suggesting some grade of sexual dysfunction [7]. The study also concluded that gynaecological and sexually transmitted infections medical history should be extended to include issues related to female sexual function".…”
Section: Discussionmentioning
confidence: 93%
“…The results of Grazyna and her colleagues study were similar with this study. They reported that satisfaction had the highest mean among the FSFI dimensions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…FSFI questionnaire is important in sexology, gynecology, and venereology [ 28 ], which consists of six domains related to sexual activity (sexual desire, sexual arousal, lubrication, orgasm, satisfaction, pain) with the total score from 2.0 to 36.0 points (Table 1 ), and a score lower than 26.55 was considered to indicate the risk of a sexual dysfunction [ 29 ].…”
Section: Methodsmentioning
confidence: 99%